Facile and green fabrication of electrospun poly(vinyl alcohol) nanofibrous mats doped with narrowly dispersed silver nanoparticles - Lin S (Dove Medical Press, 2014)
Song Lin,1,2,* Run-Ze Wang,1,2 Ying Yi,1 Zheng Wang,2,* Li-Mei Hao,2 Jin-Hui Wu,2 Guo-Han Hu,3 Hua He3,* 1National Bio-Protection Engineering Centre, Tianjin, People’s Republic of China; 2Institute of Medical Equipment, Academy of Military Medical Sciences, Tianjin, People’s Republic of China; 3Department of Neurosurgery, Changzheng Hospital, Second Affiliated Hospital of Second Military Medical University, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: Submicrometer-scale poly(vinyl alcohol) (PVA) nanofibrous mats loaded with aligned and narrowly dispersed silver nanoparticles (AgNPs) are obtained via the electrospinning process from pure water. This facile and green procedure did not need any other chemicals or organic solvents. The doped AgNPs are narrowly distributed, 4.3±0.7 nm and their contents on the nanofabric mats can be easily tuned via in situ ultraviolet light irradiation or under preheating conditions, but with different particle sizes and size distributions. The morphology, loading concentrations, and dispersities of AgNPs embedded within PVA nanofiber mats are characterized by transmission electron microscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy, ultraviolet-visible spectra, X-ray photoelectron spectroscopy, and X-ray diffraction, respectively. Moreover, the biocidal activities and cytotoxicity of the electrospun nanofiber mats are determined by zone of inhibition, dynamic shaking method, and cell counting kit (CCK)-8 assay tests. Keywords: electrospinning, silver nanoparticles, polyvinyl alcohol, nanocomposites, bioactivity